Fluorescence-detection size-exclusion chromatography utilizing nanobody technology for expression screening of membrane proteins - Fei Jin (Nature Portfolio, 2021)
To mitigate the GFP-triggered artifacts in Fluorescence-detection Size-Exclusion Chromatography (FSEC), Jin et al. develop an FSEC assay utilizing nanobody technology which allows evaluation of the expression, monodispersity and thermostability of membrane proteins without the need for purification. It holds promise as a powerful tool for screening of membrane proteins for functional and structural studies.